2008
DOI: 10.5703/1288284313445
|View full text |Cite
|
Sign up to set email alerts
|

Alternatives to Fuel Tax: a State Level Perspective

Abstract: The current and imminent revenue shortfall of the highway financing system, which is currently based on motor fuel taxes, has been widely diagnosed both at the national and state levels. A 2005 needs study assessing highway needs and future revenue during 2006-2020 for Indiana concluded that the annual funding gap during this period would be $0.86-1.12 billion. Under the current fuel-tax-based system, it is predicted that the shortfall would grow larger in the future, primarily because the current fuel tax rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…These concerns are legitimate and recent studies (Oh and Sinha, 2008;Sorensen and Taylor, 2005;Whitty, 2003) have shown that the concerns can be addressed. For instance, privacy protection could be implemented through both technological and legal means.…”
Section: Past Studies Of Alternative Highway Revenue Sourcesmentioning
confidence: 99%
See 4 more Smart Citations
“…These concerns are legitimate and recent studies (Oh and Sinha, 2008;Sorensen and Taylor, 2005;Whitty, 2003) have shown that the concerns can be addressed. For instance, privacy protection could be implemented through both technological and legal means.…”
Section: Past Studies Of Alternative Highway Revenue Sourcesmentioning
confidence: 99%
“…Furthermore, the study (TRB, 2006) concluded that cost allocation studies should be used to estimate the user fee for each vehicle class based on the damage done on the highways and finally, charging road users for vehicle miles of travel would allow for equity. Possible alternative revenue sources identified from studies (Oh and Sinha, 2008;Sisiopiku et al, 2006;Sorensen and Taylor, 2005;Whitty, 2003;Verhoef, 1997;Giuliano, 1994) include: vehicle miles of travel fees, weight-distance truck fees, tolling and congestion pricing (cordon pricing, high occupancy toll (HOT) lanes, etc).…”
Section: Past Studies Of Alternative Highway Revenue Sourcesmentioning
confidence: 99%
See 3 more Smart Citations